2018
DOI: 10.1590/s0100-83582018360100052
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic potential of Cover Crops in Control of Shrubby False Buttonweed (Spermacoce verticillata)

Abstract: potential of cover crops in control of shrubby false buttonweed ... ABSTRACT -Searching for alternatives to deal with weeds without the exclusive use of herbicides can increase the sustainability of agricultural production in the Amazon region. This study aimed to evaluate the allelopathic potential of cover crops on the weed shrubby false buttonweed (Spermacoce verticillata L.). Three straw levels (1; 2.5 and 5 mg cm -2 ) of thirteen cover crops (Cajanus cajan, Canavalia ensiformis, Crotalaria juncea, C. och… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…Although not evaluated in this research, the weed suppression observed in the treatment with M. deeringiana may have been caused by the release of allelochemicals. Several studies pointed out the allelopathic power of legumes such as M. deeringiana and C. ensiformis on other plants (Pereira et al, 2018;Vargas et al, 2018).…”
Section: /9mentioning
confidence: 99%
“…Although not evaluated in this research, the weed suppression observed in the treatment with M. deeringiana may have been caused by the release of allelochemicals. Several studies pointed out the allelopathic power of legumes such as M. deeringiana and C. ensiformis on other plants (Pereira et al, 2018;Vargas et al, 2018).…”
Section: /9mentioning
confidence: 99%
“…Porcentaje de germinación (% G) y velocidad del índice de germinación (SGI) de la hierba B. pilosa en presencia de extractos acuosos de forraje (mijo perla y crotalaria). Studies demonstrating the chemical and physical effects of cover crops of different species on invasive plants have been recurrent (5,18,21,23,26). Sturm et al (2018) claimed that knowledge of the proportions of allelopathic and competitive effects could lead to the development of cover crop consortia with optimal weed suppression characteristics in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Além do efeito físico de restrição da luminosidade, as plantas de cobertura também exercem efeito alelopático no controle de vassourinha-de-botão. Vargas et al (2018) observaram maiores inibições de germinação de vassourinhade-botão com uso de Cajanus cajan, Urochloa brizanha cv. Xaraés, Mucuna cinereum, M. aterrima, Canavalia ensiformis, Crotalaria juncea, C. spectabilis e U. ruziziensis.…”
Section: Resultsunclassified